CONSUMER RESPONS TO INSTAGRAM STORIES OF ANUGERAH TRAVELLERS THROUGH THE AIDA MODEL - Pranantya, Amira Faradhina; Sugiono, Arif; Adistya, Dyang (Jurnal Kompetitif Bisnis, 2022)
This study aims to determine consumer response to advertisements delivered and displayed by Anugerah Travellers in their Instagram stories through the AIDA model. AIDA is an acronym for attention, (making awareness of a product), interest (making interest in a product), desire (desire to own a product), and action (action in a form of buying). AIDA is a marketing strategy that is able to identify every stage experienced by a person in the purchase process for a product or service. This study uses a descriptive qualitative approach and data collection is carried out using the snowball technique plus triangulation aspects. The results of this study indicate: (1) the dimension of attention on Instagram stories uploaded by Anuegerah Travellers attracts attention or eyecatcher; (2) the dimension of interest in the Instagram stories uploaded by Anugerah Travellers are clear, good, and easy to understand; (3) the dimension of desire in Instagram stories uploaded by Anugerah Travellers can attract and increase consumer confidence; (4) the action dimension on Instagram stories uploaded by Anugerah Travellers further refines the advertisements that have been advertised in the form of purchase.